Citra Perempuan Dalam Novel Re dan Perempuan Karya Maman Suherman: Kajian Kritik Sastra Feminis - Zahrial, Agista Refi Armadani; Israhayu, Eko Sri (CV. Eduartpia Publisher, 2024)
This study is grounded in a desire to explore the portrayal of women in Indonesian literature, specifically through Maman Suherman's novel Re dan Perempuan. This novel serves as a compelling subject of study due to its complex and nuanced depiction of female characters, which reflects various issues, roles, identities, and the societal position of women. This research aims to describe and classify the image of women in the novels